Stable carbon isotope signature of methane released from phytoplankton [research data] - Klintzsch, Thomas; Geisinger, Hannah Katharina; Wieland, Anna; Langer, Gerald; Nehrke, Gernot; Bižić, Mina; Greule, Markus; Lenhart, Katharina; Borsch, Christian; Schroll, Moritz; Keppler, Frank (Universität, 2023)
Aquatic ecosystems play an important role in global methane cycling and many field studies have reported methane supersaturation in the oxic surface mixed layer (SML) of the ocean and in the epilimnion of lakes. The origin of methane formed under oxic condition is hotly debated and several pathways have recently been offered to explain the ‘methane paradox’. In this context, stable isotope measurements have been applied to constrain methane sources in supersaturated oxygenated waters. Here we present stable carbon isotope signatures for six widespread marine phytoplankton species, three haptophyte algae and three cyanobacteria, incubated under laboratory conditions. The observed isotopic patterns implicate that methane formed by phytoplankton might be clearly distinguished from methane produced by methanogenic archaea. Comparing results from phytoplankton experiments with isotopic data from field measurements, suggests that algal and cyanobacterial populations may contribute substantially to methane formation observed in the SML of oceans and lakes.
Gesehen am 12.06.2023
Keywords: Forschungsdaten; Datenbank